Rwanda : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report ;, 2020)
This paper highlights Rwanda's Request for Disbursement Under the Rapid Credit Facility (RCF). The economic impact of the coronavirus disease 2019 pandemic is rapidly unfolding with the near-term outlook deteriorating quickly. This has given a rise to significant fiscal and external financing needs. The authorities have acted fast by putting in place measures to help contain and mitigate the spread of the disease. The RCF funds will support the authorities' efforts by backstopping the decline in international reserves and providing financing to the budget for increased spending aimed at containing the epidemic and mitigating its economic impact. This additional IMF financing also ought to help catalyze further assistance from the international community, preferably in the form of grants. The IMF continues to monitor Rwanda's situation closely and stands ready to provide policy advice and further support as needed. Monetary policy needs to be data-driven and the central bank should stand ready to provide additional liquidity support if warranted. A flexible exchange rate should be maintained as a shock absorber. The National Bank of Rwanda has taken various measures to help maintain the health of the financial sector and should continue to show flexibility, while encouraging prudent loan restructuring and stepping up reporting requirements.